Nonresident Deposits in India : In Search of Return? - Gupta, Poonam (IMF Working Papers; Working Paper ;, 2004)
This paper analyzes trends in the accumulation of NRI (nonresident Indian) deposits and investigates the determinants of these inflows. It finds that monthly deposit flows have been quite stable since the 1991 crisis; nevertheless, there have been occasions when monthly flows turned negative in the short run, coinciding with adverse domestic or external events. Econometric analysis shows that the NRI deposits are influenced by standard risk and return variables. In particular, NRI deposits respond positively to changes in relative interest rates on NRI deposits and LIBOR; negatively to political and geopolitical uncertainties, such as the government resigning in mid-term, and tensions on India's borders; and negatively to adverse external events, such as the Asian crisis.